Lack of mortality in 22 children with sickle cell anemia and severe malarial anemia. Issue 1 (17th August 2017) - Opoka, Robert O.; Bangirana, Paul; Idro, Richard; Shabani, Estela; Namazzi, Ruth; John, Chandy C.
Abstract: Retrospective studies suggest that there is high mortality in children with sickle cell anemia (SCA) and severe malaria. We assessed mortality in Ugandan children with severe malarial anemia (SMA, n = 232) or cerebral malaria (CM, n = 267) by sickle cell hemoglobin genotype. Admission and 2‐year follow‐up mortality did not differ among children with SMA who had homozygous form of sickle cell hemoglobin (HbSS) versus normal form of adult hemoglobin (admission, 0/22, 0%, vs. 1/208, 0.5%; follow‐up, 1/22, 4.5%; 7/207, 3.4%, respectively; all P > 0.6). The single child with CM and HbSS survived. The study findings highlight the need for large prospective studies of malaria‐related mortality in children with SCA.